PENGARUH JENIS DAN DOSIS PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KROKOT LANDA (Talinum triangulare Willd.) - Panut Sahari (JURNAL ILMIAH AGRINECA)
The aims of the experiment were to know the effects of kinds and dosage of animal manure applications on the growth and krokot landa’s (Talinum triangulare Willd.) yield. The experiment was conducted from October until January 2005 at the dry land of Jumantono, Karanganyar regency at 180 metres above sea level. The experiment was arranged in the factorial design using Completely Randomized Block Design with 2 application factors and 9 combinations with 3 replications. Factor 1 : kinds of animal manure application consisted of 3 levels: cow manure, goat manure, chicken manure. Factor 2 : 10 ton/hectare,                         20 ton/hectare, 30 ton/hectare. The result of experiment showed that kinds of animal manure application effected to increase plant height, leaf number, the fresh and dry weight of biomass. Chicken manure could give the highest of plant height, leaf number, fresh and dry weight of biomass. Whereas animal manure dosage application effected to increase leaf number, fresh weight of leaf, fresh and dry weight of biomass. At 20 ton/hectare dosage could give the highest of leaf number, leaf’s fresh weight, fresh and dry weight of biomass. There were interactions of animal manure dosage and kinds of animal manure on the fresh weight of biomass. Chicken manure with 22.11 ton/hectare dosage could yield the maximum fresh weight of leafs and at 22.16 ton/hectare could yield the maximum fresh weight of biomass.